2019
DOI: 10.1088/1742-6596/1402/6/066066
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Kansei Engineering on academic information system interface design based on Android

Abstract: One of the goals of the Android Application is to improve the quality of the Academic Information System. This study uses the Kansei Engineering method where the emotional power of users is involved in getting design material that has a strong influence on the Android Application design concept. This study used 17 Kansei Word and 12 specimens as samples of Android applications. Kansei Word is selected from words related to an Android Application display. While specimen samples or Android applications are selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Past research adopting KE in Indonesia has been found to focus on the design of e-Learning interfaces (Griha, Isa, & Hadiana, 2017), mobile commerce (Hadiana, 2016), and Android based academic information systems design (Mud'is, Busro, Faizin, & Ali, 2019). Kholil (2017) suggested a design that translates the concept of beauty and cuteness feelings into 47 design components organised into five sections: Header, Footer, Left Sidebar, Right Sidebar, and Body.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Past research adopting KE in Indonesia has been found to focus on the design of e-Learning interfaces (Griha, Isa, & Hadiana, 2017), mobile commerce (Hadiana, 2016), and Android based academic information systems design (Mud'is, Busro, Faizin, & Ali, 2019). Kholil (2017) suggested a design that translates the concept of beauty and cuteness feelings into 47 design components organised into five sections: Header, Footer, Left Sidebar, Right Sidebar, and Body.…”
Section: Research Backgroundmentioning
confidence: 99%
“…There are several specific techniques in KE, One of them is the Kansei Engineering Type 1 or the KEPack. Technically, KEPack has several stages [6], which are defined by: 1) Determining Strategy, 2) Determining Kansei Word, 3) Arranging Semantic Differential Scale Structure, 4) Classifying Item / Category, 5) Data Evaluating, 6) Multivariate Analysis, 7) Interpreting Multivariate Analysis Result, 8) Interpreting Data to the UI Designer and 9) Designing Mockup or Prototyping…”
Section: Introductionmentioning
confidence: 99%
“…Proceedings of the 7th North American International Conference on Industrial Engineering and Operations Management, Orlando, Florida, USA, June 12-14, 2022 This approach has been used in application design research to develop food packaging (Suzianti & Aldianto 2020), educational applications and e-learning Mud'Is et al 2019;Naim & Ibrahim 2014;Nugroho et al 2019), e-commerce applications (Hadiana 2016;Lokman & Noor 2006), various service concepts (Hsiao et al 2017;Yeh & Chen 2018), knives (Razza &Paschoarelli 2015), andunderwear (Pan et al 2015). In other studies, the Kansei Engineering approach is combined with other methods to provide a more detailed explanation of user requirements, such as integration with the KANO model (Ginting & Hadiana 2018;Llinares & Page 2011), QFD model (Hartono et al 2013, and Fuzzy linguistics (Chanyachatchawan et al 2017;Kwong et al 2016;H.…”
Section: Introductionmentioning
confidence: 99%